Carta de Roberto H. Todd a Alcides Zeno - Todd, Roberto H.; Zeno, Alcides (My University, 1933)
Anecdota de Mariano Abril
Keywords: Abril Ostalo, Mariano, 1861-1935; Parra, Pancho; Todd, Roberto H.--Correspondence.; Todd, Roberto H.--Correspondencia.; Zeno, Alcides--Correspondence.; Zeno, Alcides--Correspondencia.